Analisis Komprehensif Potensi Farmakologis dan Toksisitas Senyawa Bioaktif Utama pada Kayu Bajakah (Spatholobus Littoralis Hassk): Integrasi Studi in Silico dan Bukti Empiris - Nerdy Nerdy; Nilsya Febrika Zebua; Rini Karlina Putri Zega; Nabilah Dinda Ramadani; Sara Ariska Purba; Furqaan Ali Kusuma; Dedek Andrian (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to comprehensively evaluate the potential pharmacological activities and safety profiles of seven secondary metabolite compounds (Caffeic Acid, Syringic Acid, Quercetin, Luteolin, p-Coumaric Acid, Ferulic Acid, and Epicatechin) identified in the Bajakah plant (Spatholobus littoralis Hassk.). The research approach integrates in silico analysis using the PubChem database, biological activity prediction via PASS Online, oral toxicity assessment through ProTox-II, and pharmacokinetic evaluation using pkCSM, which were subsequently validated through an empirical literature review. The results indicate that these compounds exhibit significant activity probabilities, particularly as antimutagenic, antiseptic, and antioxidant agents. Luteolin demonstrated the highest antimutagenic potential, while Quercetin showed dominant antioxidant activity. Toxicity profiling revealed that Luteolin and Caffeic Acid possess the highest safety levels (Class 5), whereas Quercetin requires special attention (Class 3). These computational findings strongly correlate with empirical evidence demonstrating that Bajakah extract exhibits broad-spectrum antibacterial activity against Staphylococcus aureus, antifungal activity against Candida albicans, as well as high antioxidant and anti-inflammatory capacities. This study provides a strong molecular foundation for the development of Bajakah as a safe and effective phytopharmaceutical candidate.